Applying a multi-criteria decision-making approach to identify key satisfaction gaps in hospital nurses' work environment. Issue 3 (March 2023) - Wang, Shiqian; Li, Lin; Liu, Chao; Huang, Lizhen; Chuang, Yen-Ching; Jin, Yanjun
Abstract: Aim: A decision analysis model was constructed to explore the key factors affecting the job satisfaction of hospital nurses and to analyze the key satisfaction gaps in the case hospital. Background: In China, medical institutions are facing greater pressure and challenges in the normalization of epidemic prevention and control. Nurses play a critical role in the delivery of medical care services. Past studies have shown that improving job satisfaction among hospital nurses is important for both reducing nurse turnover and improving the quality of care. Methods: McCloskey/Mueller satisfaction scale (MMSS-31) was used to survey 25 nursing specialists in a case hospital in Zhejiang. Then, the Consistent Fuzzy Preference Relation (CFPR) method was used to analyze the degree of importance of dimensions and corresponding sub-criteria. Finally, the importance-performance analysis method was applied to identify critical satisfaction gaps for the case hospital. Results: In terms of local weight for dimensions, "Control/Responsibility ( C 8 )" ≻ "Praise/Recognition ( C 7 )" ≻ "Extrinsic Rewards ( C 1 )" are the top three key factors for nurses' work environment satisfaction in the case of a hospital. In addition, the sub-criteria "Salary ( C 11 )", "Benefits ( C 13 )", "Child care ( C 33 )", "Recognition-peers ( C 73 )", "Encouragement/feedback ( C 74 )", and "Decision making ( C 85 )" are the key factors for improving clinical nursing satisfaction in the case hospital. Conclusion: The issues that nurses care about but for which they have not attained expectations mainly involved extrinsic rewards, recognition/encouragement and control over their working process. The findings of this study could offer an academic reference for management and remind them to consider the above factors in exploring future reform, further improving nurses' job satisfaction and motivating them to provide better nursing services. Highlights: McCloskey/Mueller satisfaction scale is a common measure of nurse job satisfaction, and past studies have been based on statistical analysis methods to explore the relationship between indicators. However, the application of multi-criteria decision-making methods to further construct a quantitative decision-making model has been rarely applied to case analysis. In this study, an optimal pairwise comparison method (i.e., Consistent Fuzzy Preference Relation, CFPR) was used, which greatly reduces the number of questions and the advantages of complete consistency compared to the traditional analytic hierarchy process method. This study uses importance-performance analysis as an evaluation framework and CFPRs as a weighted approach, and the combination of methods can help decision makers easily identify performance gaps in key satisfaction and propose various strategies for improvement.